1998
DOI: 10.1002/(sici)1096-9136(199804)15:4<320::aid-dia563>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of soluble CD23 serum levels and cell-surface CD23-expression in subjects at increased risk of Type 1 diabetes mellitus and in diabetic patients

Abstract: The low affinity receptor for IgE, CD23, is expressed on lymphocytes among other cell types. The purpose of the present study was to assess serum sCD23 levels and CD23 expression on peripheral blood mononuclear cells (PBMC) in people at increased risk of developing Type 1 diabetes mellitus and in diabetic patients. Serum sCD23 levels were significantly higher in first-degree relatives of Type 1 patients (median: 3.2 U ml(-1)) (p < 0.001) and in newly diagnosed (median: 3.3 U ml(-1)) (p < 0.001) and long-standi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…Differences in the stage of the autoimmune process cannot contribute to contrasting results from Avanzini et al . [19], as speculated [16]. Indeed, the duration of disease in our study covers a very wide range, yet we found no association with CD23 expression.…”
Section: Discussionsupporting
confidence: 66%
“…Differences in the stage of the autoimmune process cannot contribute to contrasting results from Avanzini et al . [19], as speculated [16]. Indeed, the duration of disease in our study covers a very wide range, yet we found no association with CD23 expression.…”
Section: Discussionsupporting
confidence: 66%